Nursing Intervention to Improve the Caregivers’ Practices toward Elderly Care at Geriatric Homes - Sanya Zakarya Mohammed; Magda Abdelsattar Ahmad; Nadia Hamed Farahat (Indian Journal of Forensic Medicine & Toxicology, 2021)
Population ageing is a global phenomenon with the number of persons 60 years and over estimated to reachtwo billion by the year 2050; living longer is joined to challenges of disability and being dependent oncaregivers who should have the chance to perform their practices by professional way as an integral partof elderly care. Aim: To evaluate the nursing intervention program to improve the caregivers’ practices ofelderly care at geriatric homes. Design: Quasi-experimental research design. Setting: In geriatric homes atCairo governorate. Sample: A convenient sample of all elderly caregivers working in the previous mentionedsettings. Tool: Was used an interviewing questionnaire to assess socio-demographic characteristics ofelderly caregivers, their knowledge, their practices & factors causing stress to them & their coping withstress. Conclusion: The nursing intervention program implementation had statistically significant positiveeffect on elderly caregivers at geriatric homes regarding to their knowledge, practices &coping with stress.